Pencapaian Prestasi Olahraga Bola Voli Melalui Pembinaan - Balkis Ratu NL Esser (Lembaga Penelitian dan Pendidikan Mandala, 2019)
Regarding to the system of national sport legislation, the development of sport begins to be taken seriously. The club style development is applied in European countries, while the United States of America applies the school style development. Volleyball has different characteristics and problems, so it takes a special treatment in order to improve the development of volleyball optimally. Based on the statement that all systems will not be perfect, the two lines of development above will be a challenge to choose which one is appropriate to apply. The development of volleyball in Indonesia generally divided into clubs and education. Adapting the two types of sport development will make the existence of volleyball development system better.